Bacterial microbiome diversity along poultry slaughtering lines: insights from chicken carcasses and environmental sources - Telli Arife Ezgi; Biçer Yusuf; Telli Nihat; Sönmez Gonca; Turkal Gamze; Güzel İsmail (Journal of Veterinary Research)
This study aimed to determine the bacterial diversity of chicken carcasses and their surrounding environment at various stages along a poultry slaughter line.